Risk Aversion and Wealth Effects on Portfolios with Many Assets: An Extension - Long, Ngo Van (Review of Economic Studies, 1975)
Risk Aversion and Wealth Effects on Portfolios with Many Assets: An Extension Get access Ngo van Long Ngo van Long Australian National University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 473–477, https://doi.org/10.2307/2296860 Published: 01 July 1975